Effectiveness of Watching a Kumagai Method Video for Long-Nipple Bottle-Feeding for Children with Cleft Lip and Palate: A Pilot Experimental Before–After Trial Study - Shingo Ueki; Yukari Kumagai; Yumi Hirai; Eri Nagatomo; Shoko Miyauchi; Takuro Inoue; Qi An; Eri Tashiro; Junko Miyata (Children)
Aim: This study aimed to determine whether the Kumagai method could be followed by watching an instructional video and to compare the feeding actions of specialists and the general population. Materials and Methods: Eleven adults from diverse backgrounds were recruited and asked to feed a baby doll using a bottle feeder with a long nipple, and their actions were recorded. Then, they watched a 2.5-min instructional video of the Kumagai method and were asked to bottle-feed again. Video recordings of the participants were used to evaluate whether their actions followed the Kumagai method. Differences in the feeding actions of the specialists and participants were determined from still images in the videos. The McNemar test was used to analyze the differences between the participants’ actions before and after. The Kruskal–Wallis test was also used to determine differences between the actions of participants and specialists. Results: Feeding movements significantly improved after watching the video. Participants’ actions, which differed significantly from those of the specialists, were evident in “the angle of the nipple at the moment the nipple was brought close to the lips” and “the angle change of the nipple from the lip to the mouth”. Conclusions: Watching our short instructional video was effective in improving the technique of the Kumagai method; however, it is insufficient for feeding a real child with cleft lip and palate. Including the rationale of each action in the video and adding direct instruction as a supplement is required.